Clustering of Tissue-Specific Sub-TADs Accompanies the Regulation of HoxA Genes in Developing Limbs - Berlivet, Soizik (Public Library of Science, 2013)
HoxA genes exhibit central roles during development and causal mutations have been found in several human syndromes including limb malformation. Despite their importance, information on how these genes are regulated is lacking. Here, we report on the first identification of bona fide transcriptional enhancers controlling HoxA genes in developing limbs and show that these enhancers are grouped into distinct topological domains at the sub-megabase scale (sub-TADs). We provide evidence that target genes and regulatory elements physically interact with each other through contacts between sub-TADs rather than by the formation of discreet “DNA loops”. Interestingly, there is no obvious relationship between the functional domains of the enhancers within the limb and how they are partitioned among the topological domains, suggesting that sub-TAD formation does not rely on enhancer activity. Moreover, we show that suppressing the transcriptional activity of enhancers does not abrogate their contacts with HoxA genes. Based on these data, we propose a model whereby chromatin architecture defines the functional landscapes of enhancers. From an evolutionary standpoint, our data points to the convergent evolution of HoxA and HoxD regulation in the fin-to-limb transition, one of the major morphological innovations in vertebrates.